HIF2 Regulates Intestinal Wnt5a Expression - García García, Carolina J.; Acevedo Diaz, Ariana C.; Kumari, Neeraj; Govindaraju, Suman; de la Cruz Bonilla, Marimar; San Lucas, F. Anthony; Nguyen, Nicholas D.; Jiménez Sacarello, Iancarlos; Piwnica-Worms, Helen; Maitra, Anirban; Taniguchi, Cullen M. (Frontiers in Oncology, 2021)
Radiation therapy for abdominal tumors is challenging because the small intestine is exquisitely radiosensitive. Unfortunately, there are no FDA-approved therapies to prevent or mitigate GI radiotoxicity. The EGLN protein family are oxygen sensors that regulate cell survival and metabolism through the degradation of hypoxia-inducible factors (HIFs). Our group has previously shown that stabilization of HIF2 through genetic deletion or pharmacologic inhibition of the EGLNs mitigates and protects against GI radiotoxicity in mice by improving intestinal crypt stem cell survival. Here we aimed to elucidate the molecular mechanisms by which HIF2 confers GI radioprotection. We developed duodenal organoids from mice, transiently overexpressed non-degradable HIF2, and performed bulk RNA sequencing. Interestingly, HIF2 upregulated known radiation modulators and genes involved in GI homeostasis, including Wnt5a. Non-canonical Wnt5a signaling has been shown by other groups to improve intestinal crypt regeneration in response to injury. Here we show that HIF2 drives Wnt5a expression in multiple duodenal organoid models. Luciferase reporter assays performed in human cells showed that HIF2 directly activates the WNT5A promoter via a hypoxia response element. We then evaluated crypt regeneration using spheroid formation assays. Duodenal organoids that were pre-treated with recombinant Wnt5a had a higher cryptogenic capacity after irradiation, compared to vehicle-treated organoids. Conversely, we found that Wnt5a knockout decreased the cryptogenic potential of intestinal stem cells following irradiation. Treatment with recombinant Wnt5a prior to irradiation rescued the cryptogenic capacity of Wnt5a knockout organoids, indicating that Wnt5a is necessary and sufficient for duodenal radioprotection. Taken together, our results suggest that HIF2 radioprotects the GI tract by inducing Wnt5a expression.